Consultation-Liaison Psychiatry Services in Ireland: A National Cross-Sectional Study - Doherty, Anne M.; Plunkett, Rosie; McEvoy, Katherine; Kelleher, Eric; Clancy, Maurice; Barrett, Elizabeth; Greene, Elaine; Cassidy, Eugene; Lee, William; MacHale, Siobhan (Frontiers in Psychiatry, 2021)
Objective: This study aimed to describe the provision of consultation-liaison psychiatry (CLP, also known as liaison psychiatry) services in acute hospitals in Ireland, and to measure it against recommended resourcing levels. Methods: This is a survey of all acute hospitals in Ireland with Emergency Departments, via an electronic survey sent by email and followed up by telephone calls for missing data. Data were collected on service configuration, activity, and resourcing. Data were collected from CLP or proxy services at all acute hospitals with an Emergency Department in Ireland (n = 29). This study measured staffing and activity levels where available. Results: None of the services met the minimum criteria set out by either national or international guidance per 500 bed general hospital. Conclusions: CLP is a relatively new specialty in Ireland, but there are clear international guidelines about the staffing levels required to run these services safely and effectively. In Ireland, despite clear national guidance on staffing levels, no services are staffed to the levels suggested as the minimum. It is likely that patients in Ireland's acute hospitals have worse outcomes, and hospitals have unnecessary costs, due to this lack. This is the first study of CLP provision in Ireland and demonstrates the resource constraints under which most services work and the heterogeneity of services nationally.